Implementation of BLAKE3 hashing for accelerating digital evidence integrity verification in forensic investigations - Mirza Gofur Saleh; H.A. Danang Rimbawa (Institute of Computer Science (IOCS), 2026)
The evolution of cybersecurity threats demands rapid and legally accountable investigation responses. A crucial principle in digital forensics is maintaining data integrity to ensure the validity of the chain of custody in court using cryptographic hash functions. However, the increasing volume of storage media presents significant technical challenges. Conventional algorithms like SHA-256 process data sequentially, causing hash verification on massive forensic images to take hours. This study aims to evaluate the BLAKE3 algorithm as an accelerator in the digital evidence integrity verification process. The evaluation was conducted using a comparative experimental method between MD5, SHA-256, and BLAKE3 by varying processor core allocations and simulated file sizes up to 50 GB. The test results demonstrated that parallel processing in BLAKE3 significantly reduces execution time. In the 50 GB file test utilizing 8 threads, BLAKE3 achieved a throughput of 5000 MB/s and completed verification in just 10.0 seconds, vastly outperforming SHA-256 which required 142.8 seconds. The application of BLAKE3 proved to provide security equivalent to SHA-256 while accelerating the verification process, thereby supporting more efficient courtroom proceedings without violating legal integrity standards.